The Influence of Teachers’ Competence in Modern Era On Young Children’s Motivation And Role-Play Activities - Nurdin, Nurdin (Murhum : Jurnal Pendidikan Anak Usia Dini, 2024)
The study aims to analyze the influence of teachers’ competence in the modern era on young children's motivation and role-play activities at TK/RA (Kindergarten) Tri Putri, Makassar City. The method employed in this study was quantitative with associative design, which aims to identify the influence between two or more variables. The variables of this study were teachers’ competence, motivation, and role-play activity. The populations and samples were 43 TK/RA Tri Putri Kota Makassar students selected purposively. This study analyzed the data through Partial Least Square (PLS). The findings show that: 1) motivation influences the play role activities, meaning that the higher the role-play activities, the higher the motivation; 2) teachers’ competence influences the motivation, meaning that the higher the teachers’ competence, the bigger the motivation; 3) teachers’ competence influence the role-play activities. It means that the higher the teacher’s competence, the higher the role-play activities; 4) role-play activities could mediate teachers' competence on motivation.